Wartości muzykoterapii stosowanej u osób z niepełnosprawnością = Importance of music therapy used in patients with disabilities - Cesarz, Helena (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
Music therapy, as a form of comprehensive treatment, is used in medical, psychological and pedagogical treatment, as well as in rehabilitation, education and the health promotion, prevention and recreation. It has been included in the university programme of study in 1950 in the United States.
Keywords: muzykoterapia; techniki muzykoterapii; osoby z niepełnosprawnością; music therapy; music therapy techniques; people with disabilities